Using civil society as an authoritarian legitimation strategy: Algeria and Mozambique in comparative perspective. Issue 6 (19th September 2017) - Lorch, Jasmin; Bunk, Bettina
Abstract : Recent research on civil society in authoritarian regimes shows that civil society can contribute to legitimating authoritarian rule. This finding has not, however, been connected with the nascent literature on authoritarian regime legitimation. This article seeks to bridge this gap by synthesizing the relevant theoretical literature and presenting an in-depth comparative analysis of Algeria and Mozambique. We argue that in both cases the ruling authoritarian regime has used civil society as a legitimation tool. The article identifies five patterns according to which authoritarian regimes can use civil society for legitimation purposes.